Spiritualitás a vallásfenomenológia és pasztorálpszichológia horizontján - KOVÁCS, Szabolcs (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2021)
Spirituality at the Horizon of Religious Phenomenology and Pastoral Psychology. We are living in a designer world, where not only the circumstances but our gods will be created consciously. We hunger for a God. Choosing an inadequate god, a god too small to transcend our limitations and who therefore can neither save nor transform us, drives us to keep hunting. This study reviews the phe-nomenology of Christian spirituality, religious practice and places special em-phasis on these areas. We can find a correlation between spirituality and spiritu-al well-being and happiness, factors which contribute to a positive personal de-velopment. We are condemned to meaning. There is a universal impulse to as-sign meaning to our joys and sorrows. Christian spirituality is a condition for us to reframe and understand our life perspectives and reach the “Courage to be” (Tillich).